Functional nanomaterials, synergisms, and biomimicry for environmentally benign marine antifouling technology. Issue 12 (2nd November 2021) - Kumar, Avishek; AL-Jumaili, Ahmed; Bazaka, Olha; Ivanova, Elena P.; Levchenko, Igor; Bazaka, Kateryna; Jacob, Mohan V.
Abstract : This review outlines recent progress and strategies for highly efficient, environmentally-friendly marine antifouling technology based on nanomaterials and nanocomposites, as well as synergistic and biomimetic approaches. Abstract : Marine biofouling remains one of the key challenges for maritime industries, both for seafaring and stationary structures. Currently used biocide-based approaches suffer from significant drawbacks, coming at a significant cost to the environment into which the biocides are released, whereas novel environmentally friendly approaches are often difficult to translate from lab bench to commercial scale. In this article, current biocide-based strategies and their adverse environmental effects are briefly outlined, showing significant gaps that could be addressed through advanced materials engineering. Current research towards the use of natural antifouling products and strategies based on physio-chemical properties is then reviewed, focusing on the recent progress and promising novel developments in the field of environmentally benign marine antifouling technologies based on advanced nanocomposites, synergistic effects and biomimetic approaches are discussed and their benefits and potential drawbacks are compared to existing techniques.